The contributions of Enactus to South Africa’s social and solidarity economy: a case study of a university - Ndlovu, Crespen; Lefera, Maraka (OASIS, 2024)
𝗕𝗮𝗰𝗸𝗴𝗿𝗼𝘂𝗻𝗱: Over the past decade, there has been a noticeable rise in worldwide acknowledgement of the Social and Solidarity Economy (SSE) and its substantial socioeconomic and environmental benefits. In response, the United Nations General Assembly (UNGA) passed a resolution on 18 April 2023 advocating for government and institutional support to the SSE towards accelerating the achievement of sustainable development Goals (SDGs). However, there is a lack of understanding of how higher education institutions contribute to this agenda. 𝗔𝗶𝗺:The study examines the contributions of Entrepreneurial Action Us (Enactus) to South Africa’s SSE. 𝗦𝗲𝘁𝘁𝗶𝗻𝗴: The case study was conducted at the Central University of Technology (CUT), Free State in South Africa, to examine how higher education and the SSE interact through Enactus initiatives. 𝗠𝗲𝘁𝗵𝗼𝗱𝘀: The study utilised a qualitative research design involving semi-structured interviews with 11 students and alumni and an analysis of Enactus’ annual impact reports. This allowed for a comprehensive understanding of participants’ experiences and perceptions regarding Enactus’ impact on the SSE. 𝗥𝗲𝘀𝘂𝗹𝘁𝘀: Enactus enhances student entrepreneurship and innovation, promoting economic growth, job creation and community sustainability. Initiatives like the student-led Vermi Village Enterprise have empowered youth and women and created employment opportunities. Collaboration with local corporations and educational institutions has fostered sustainable changes, improving regenerative agriculture and urban food production, thus addressing multiple poverty facets. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻: This study highlights the crucial role of initiatives like Enactus in promoting a more inclusive and sustainable economy, advancing the broader objectives of the SDGs, and supporting a brighter future for South Africa. 𝗖𝗼𝗻𝘁𝗿𝗶𝗯𝘂𝘁𝗶𝗼𝗻: Despite resource limitations and the need for greater stakeholder engagement, Enactus projects and enterprises hold significant potential for driving sustainable development and socioeconomic equality, ultimately strengthening South Africa’s SSE.
Keywords: Entrepreneurship; Social and solidarity economy; Enactus; Sustainable development goals; Students